2012
DOI: 10.1002/anie.201208120
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Stereoselective Semihydrogenation of Alkynes to E‐Alkenes

Abstract: Scheme 2. Bargon's proposed dinuclear mechanism for the Cp*Rucatalyzed E-selective reduction. Cp* = pentamethylcyclopentadienyl. Scheme 3. Fürstner's functional-group-tolerant trans hydrogenation (yield is a combination of E/Z stereoisomers and the alkane (5-15 %, as determined by GC analysis)). Tf = trifluoromethanesulfonyl. Angewandte Chemie 807

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
29
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 26 publications
1
29
0
Order By: Relevance
“…The olefin insertion into a MH bond is a key step in the catalytic cycles proposed for olefin functionalization reactions and leads to the formation of alkyl metal intermediates . The acetylene insertion into the MH bond also plays an important role in a number of catalytic processes, such as hydrogenation or polymerization reaction, which receives considerable attention due to its utility in organic syntheses . However, the addition of 1 equiv of alkynes into several polyhydride complexes leads to the displacement of H 2 from the metal center, rather than the insertion into the MH bond, unless the alkenes or alkynes contain strong electron‐withdrawing groups, such as CO 2 Me, CO 2 t Bu, CO 2 TMS, and so on .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The olefin insertion into a MH bond is a key step in the catalytic cycles proposed for olefin functionalization reactions and leads to the formation of alkyl metal intermediates . The acetylene insertion into the MH bond also plays an important role in a number of catalytic processes, such as hydrogenation or polymerization reaction, which receives considerable attention due to its utility in organic syntheses . However, the addition of 1 equiv of alkynes into several polyhydride complexes leads to the displacement of H 2 from the metal center, rather than the insertion into the MH bond, unless the alkenes or alkynes contain strong electron‐withdrawing groups, such as CO 2 Me, CO 2 t Bu, CO 2 TMS, and so on .…”
Section: Introductionmentioning
confidence: 99%
“…[7,8] The acetylene insertion into the M H bond also plays an important role in a number of catalytic processes, such as hydrogenation or polymerization reaction, which receives considerable attention due to its utility in organic syntheses. [9][10][11] However, the addition of 1 equiv of alkynes into several polyhydride complexes leads to the displacement of H 2 from the metal center, rather than the insertion into the M H bond, unless the alkenes or alkynes contain strong electron-withdrawing groups, such as CO 2 Me, CO 2 t Bu, CO 2 TMS, and so on. [12][13][14][15] Komine and coworkers also reported the insertion of selective alkenes into inert M H bonds of molybdenum and tungsten hydrides MHCp(CO) 3 (M Mo, W) catalyzed by palladium(0) complexes, and showed that (Z)-and (E)-alkenes (MeO 2 CC CCO 2 Me) can be easily inserted into the Mo/W H bonds and have a high reaction rate and yield.…”
Section: Introductionmentioning
confidence: 99%
“…[3] We reasoned that semihydrogenation of alkynes would be both ac hallenging and meaningful playground for aromatic palladium clusters. [4] Whereas these reactions are wells tudied in homogenous catalysis, [5] no catalytic methodf or the semireductiono fa lkynes has been reportedb yu sing discrete Pd clusters,a nd examples with other clusters are rare. [6] (Z)-Alkenes can be formed in high yields by using electron-rich Pd 0 complexes bearing suitable N-heterocyclic carbenes or chelating diphosphinesa sl igands.…”
mentioning
confidence: 99%
“…This was surprising, as the two clusters have nearly identicals tructural and electronic features [3] and low-valent Pt complexes can be efficient reduction catalysts (for ap ossible rationalization see below). [4] We next examined av ast array of aromatic alkynes ( Table 2). Increasingt he length of the aliphatic arm demandedalonger reactiont ime to reach full conversion ( Table 2, entries 3a nd 4).…”
mentioning
confidence: 99%
“…Considering the fact that high E-stereoselective semireduction of a triple bond is an important goal of contemporary organic chemistry [7][8][9][10][11][12][13][14] , herein, we wish to report the development of such a highly selective copper(I)-catalysed tandem three-component coupling-semireduction reaction of commercially readily available terminal alkynes, aldehydes and 3-pyrroline or isoindoline affording N-allyl amines with an E-C ¼ C bond (Fig. 1b).…”
mentioning
confidence: 99%